Automotive control systems : for engine, driveline, and vehicle - Kiencke, U.; Nielsen, Lars, 1955- (Berlin : New Delhi : Springer, 2005)
Reflecting the trend to optimization through integrative approaches for engine, driveline and vehicle control, this book enables control engineers to understand engine and vehicle models necessary for controller design and also introduces mechanical engineers to vehicle-specific signal processing and automatic control.
Thermodynamic Engine Cycles.- Engine Management Systems.- Diesel Engine Modeling.- Engine Control Systems.- Diagnosis.- Driveline Control.- Vehicle Modelling.- Vehicle Parameters and States.- Vehicle Control Systems.- Road and Driver Models.
Includes bibliographical references and index.
Keywords: Automobiles -- Automatic control; Adaptive control systems; Automobiles -- Motors -- Control systems